2013
DOI: 10.1093/restud/rdt035
|View full text |Cite
|
Sign up to set email alerts
|

Pounds That Kill: The External Costs of Vehicle Weight

Abstract: Heavier vehicles are safer for their own occupants but more hazardous for other vehicles. Simple theory thus suggests that an unregulated vehicle fleet is inefficiently heavy. Using three separate identification strategies we show that, controlling for own-vehicle weight, being hit by a vehicle that is 1,000 pounds heavier generates a 40-50% increase in fatality risk. These results imply a total accident-related externality that exceeds the estimated social cost of U.S. carbon emissions and is equivalent to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(42 citation statements)
references
References 35 publications
6
36
0
Order By: Relevance
“…As seen from Fig.6, ϕ 1 direction is along the horizontal axis whereas Φ direction lays in the vertical axis. Based on the Euler angles the texture intensity was much lower in the ZEK100 alloy than in the RE-free Mg alloys, e.g., 8.5~8.9 MRD in the AM30 alloy [57]. This observation supported the suggestion of texture weakening when RE elements were added in Mg alloys.…”
Section: Crystallographic Texturesupporting
confidence: 64%
“…As seen from Fig.6, ϕ 1 direction is along the horizontal axis whereas Φ direction lays in the vertical axis. Based on the Euler angles the texture intensity was much lower in the ZEK100 alloy than in the RE-free Mg alloys, e.g., 8.5~8.9 MRD in the AM30 alloy [57]. This observation supported the suggestion of texture weakening when RE elements were added in Mg alloys.…”
Section: Crystallographic Texturesupporting
confidence: 64%
“…Some authors have found evidence that SUVs are particularly harmful to occupants of ordinary cars (Anderson and Auffhammer 2011;White 2004), but these studies used data on accidents from earlier years than those in the current study. Some authors have found evidence that SUVs are particularly harmful to occupants of ordinary cars (Anderson and Auffhammer 2011;White 2004), but these studies used data on accidents from earlier years than those in the current study.…”
Section: A Two-vehicle Crashesmentioning
confidence: 99%
“…Policy emphasis has thus centered on whether a gasoline tax could accomplish much the same end since heavier vehicles use more gasoline per mile traveled and would thus pay a higher per mile tax rate (Anderson and Auffhammer 2011). Policy emphasis has thus centered on whether a gasoline tax could accomplish much the same end since heavier vehicles use more gasoline per mile traveled and would thus pay a higher per mile tax rate (Anderson and Auffhammer 2011).…”
Section: Figure 3 External Safety and Environmental Costs Per Mile Drmentioning
confidence: 99%
See 1 more Smart Citation
“…per ton (Parry, Walls, and Harrington 2007, 377), while other analyses of the combined costs of local pollution, congestion, and accident externalities have arrived at estimates as high as $2.40 per gallon (M. L. Anderson and Auffhammer 2013;Parry, Walls, and Harrington 2007).…”
Section: The Energy-efficiency "Gap"mentioning
confidence: 99%